Patient centered collaborative care approach to medical-surgical nursing volume 1 - Ignatavicius, Donna D.; Workman, M. Linda (Singapore : Saunders Elsevier, 2010)
Cutting-edge, evidence-based content covers the core body of knowledge for medical-surgical nursing, all in one easy-to-understand reader-friendly textbook.
Foundations for medical surgical nursing -- Concepts of emergency care and disaster preparedness -- Management of patients with fluid, electrolyte and acid-base imbalances -- Management of perioperative patients -- Problems of protection : management of patients with problems of the immune system -- Problems of protection : management of patients with problems of the skin, hair and nails -- Problems of oxygenation : management of patients with problems of respiratory tract -- Problems of cardiac and tissue perfusion : management of patients with problems of the cardiovascular system -- Problems of tissue perfusion : Management of patients with problems of the hematologic system -- Problems of mobility, sensation, and cognition : management of patients with problems of the nervous system -- Problems of sensations : management of patients with problems of the sensory system -- Problems of mobility : management of patients with problems of the musculoskeletal system -- Problems of digestion, nutrition, and elimination -- Problems of regulation and metabolism -- Problems of excretion -- Problems of reproduction.
Includes index.
Keywords: NURSING